2019
DOI: 10.21873/anticanres.13873
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Accumulation of β-Catenin in Cancer Stem Cell Radioresistance and Stemness in Human Colon Cancer

Abstract: Background/Aim: The aim of this study was to examine whether the Wnt/β-catenin signal activation is a cause of radioresistance in colon cancer by assessing the β-catenin localization and its correlation with cancer stem cells (CSCs). Materials and Methods: The nuclear levels of β-catenin, the hallmark of Wnt activation, were analyzed in HCT116 and SW480 cells by immunohistochemistry, before and after irradiation. Further, we assessed CSC populations by staining for aldehyde dehydrogenase-1 (ALDH1) and CD44. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Increasing evidence suggest that the Wnt/β-catenin pathway is associated with radioresistance of cancer cells (7,30). The enhanced nuclear translocation of β-catenin was more evident in radioresistance cells (31)(32)(33). Consistent with these findings, the present study demonstrated that Wnt5a knockdown decreased nuclear β-catenin expression, whereas overexpression of Wnt5a enhanced nuclear β-catenin expression.…”
Section: Discussionsupporting
confidence: 90%
“…Increasing evidence suggest that the Wnt/β-catenin pathway is associated with radioresistance of cancer cells (7,30). The enhanced nuclear translocation of β-catenin was more evident in radioresistance cells (31)(32)(33). Consistent with these findings, the present study demonstrated that Wnt5a knockdown decreased nuclear β-catenin expression, whereas overexpression of Wnt5a enhanced nuclear β-catenin expression.…”
Section: Discussionsupporting
confidence: 90%
“…ALDH1 plays a vital role in CRC and promotes the metastasis and proliferation of CRC stem cells through various classical pathways. Studies have suggested that the high expression of ALDH1 in CRC is related to the Wnt/β-catenin pathway ( 82 , 89 , 90 ), hsa_circ_0001806/miR-193a-5p/, COL1A1 axis ( 89 ), PI3K/AKT/mTOR signaling pathway ( 91 ), CXCL2/CXCR2 axis ( 92 ), miR-200-ZEB1/SANI2 axis ( 88 ). Additionally, ALDH1B1 may maintain the CSC phenotype and promote cancer cell growth by protecting cells from DNA damage ( 87 ).…”
Section: Aldh1 and Various Solid Tumorsmentioning
confidence: 99%
“…The loss of E-cadherin, mediated by these non-coding RNAs [188], promotes β-catenin release into the cytoplasm [189]. Once translocated to the nucleus, β-catenin downregulates not only cell-junction-related genes (E-cadherin and claudin-7) [89,190] but also upregulates stemness-related genes, facilitating the formation of CSCs [191][192][193].…”
Section: Exosomes In Cancer Stem Cell (Csc) Formationmentioning
confidence: 99%